Evolution and determinants of sustainability of journal club in Nigerian postgraduate medical training institutions - Terhemen J. Igbudu; Livinus Egwuda; Osarieme E Omokhua; James Mngutyo (Universiti Kebangsaan Malaysia, 2015)
Journal club is a veritable medium for knowledge creation especially at the postgraduate-level training in different fields of human endeavor. There are very few successful journal clubs unlike many postgraduate medical training institutions, and despite its being indispensible, the concept of journal club remains an area that has been ill-researched. The success of the evolved journal club till today is hampered by many factors. Some of these determinants are general apathy to attending sessions, lack of time, and inadequate preparations. Sustainable developmental theory was used to analyze the primary and secondary data collected. It was however clear that the success of the journal club was dependent on the beneficiaries, training institutions, and the respective bodies that oversee those training programs. It is therefore important that adequate research attention is given to this area to prevent it from going into extinction, which is the thrust of this article.